1995
DOI: 10.1111/j.1748-0361.1995.tb00406.x
|View full text |Cite
|
Sign up to set email alerts
|

Access to Health Care: Urban‐Rural Comparisons from a Midwestern Agricultural State

Abstract: Lack of access to quality health care for a large number of Americans, particularly those living in rural areas, is a major health care problem. Differences in access between rural and urban areas are caused by obstacles to providing adequate care, such as hospital closures and physician shortages, and low income and/or employment that does not provide health insurance as an employee benefit. This study, based on a random sample of 6,000 households in Nebraska, finds that access to health care is better for re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 12 publications
0
33
1
Order By: Relevance
“…15, 16 Among nonelderly adults in Nebraska, rural residents were more likely than MSA residents to have a personal physician and made a greater number of physician visits. 17 In contrast, studies of the elderly found that the likelihood of having any outpatient event was greater in non-metropolitan than metropolitan places, 9 and the mean number of ambulatory visits was lower among residents of nonmetropolitan counties than large metropolitan core and fringe counties 16 or central city residents. 18 Rural-urban location is often measured dichotomously, by comparing residents of MSAs to those who live outside an MSA.…”
mentioning
confidence: 92%
“…15, 16 Among nonelderly adults in Nebraska, rural residents were more likely than MSA residents to have a personal physician and made a greater number of physician visits. 17 In contrast, studies of the elderly found that the likelihood of having any outpatient event was greater in non-metropolitan than metropolitan places, 9 and the mean number of ambulatory visits was lower among residents of nonmetropolitan counties than large metropolitan core and fringe counties 16 or central city residents. 18 Rural-urban location is often measured dichotomously, by comparing residents of MSAs to those who live outside an MSA.…”
mentioning
confidence: 92%
“…Norton and McManus (1989) and Moscovice (1989) reported that Medicare beneficiaries in rural areas had more discharges per capita than urban residents, but recent studies show no significant differences in hospital use between urban and rural residents (Himes & Rutrough, 1994;Comer & Mueller, 1995). Rural hospitals, as compared to urban hospitals, have fewer beds (Moscovice, 1989), lower occupancy rates (Mick & Morlock, 1990) and shorter lengths of stay (Mick & Morlock, 1990).…”
Section: Urban and Rural Differences In Health Service Usementioning
confidence: 99%
“…Despite considerable improvements in health service delivery to rural communities, this question remains unanswered, in part due to conflicting reports on differences in health service use by rural and urban elderly persons (Comer & Mueller, 1995;Dubay, 1993;Himes & Rutrough, 1994;Kenney, 1993).…”
mentioning
confidence: 99%
“…Similarly a study in Nebraska comparing urban and rural settings showed that access to health care in rural Nebraska was as good, if not better, than access to health care in urban parts of the same state. 48 …”
Section: Rehabilitation In Rural Settingsmentioning
confidence: 99%